Design, Manufacturing and Tribological Performance of Microtextured Bucket Tappets for Friction Reduction in the Valve Train - Marian, Max; Zahner, Michael; Tremmel, Stephan; Andreas, Kolja; Merklein, Marion; Wartzack, Sandro (6th World Tribology Congress, 2017)
In order to improve lubricating conditions as well as friction and wear behavior, the surfaces of contacting bodies in lubricated tribological contacts can be microtextured. While this approach has already reached industrial application for lower loaded contacts, the effects for higher loaded contacts, where elastic deformation plays a significant role, are still topic of basic research. For this reason, microtextures are adapted to the conditions of the tribological system of the bucket tappet/camshaft contact in the valve train as a demonstrator and major contributor to combustion engine losses. The tribological performance of various microtexture geometries and arrangements is analyzed on a one bucket tappet/one cam test-rig using series production valve train parts. A resistive measurement system is first applied to the highly dynamic tappet/camshaft contact and allows the investigation of the correlation between lubricating conditions and friction force. In the tests, a significant friction force reduction using microtextured surfaces compared to polished surfaces is achieved. Additionally, quantitative ex-situ wear characterization is carried out for long-run test cycles, using Laser Scanning Microscopy. Thus, wear mechanisms and rates are compared with the measurements of lubricating conditions and friction force. Besides the identification of advantageous microtexture geometries and arrangements regarding the tribological performance, possibilities and limitations of the manufacturing technology are examined. In order to realize high-volume production, a micro coining process was studied. In this regard the manufacturing of the coining punch using µEDM and the coining process itself were analyzed with respect to accuracy and reproducibility. Additionally, the durability of the pins was investigated for the micro coining process. The limitations of the manufacturing process and of the micro coining process are summarized in a process windo
Keywords: Microtextures; Micro Coining; EHL Contact